Platycuma bamberconfabulor sp. nov. (Crustacea: Cumacea: Nannastacidae) from Antarctica, with a note on the gut of Platycuma - Gerken, Sarah; Watling, Les (Zootaxa, 2015)
Platycuma bamberconfabulor sp. nov. is based on a specimen from the Ross Sea. The species can be distinguished from the other species in the genus through the combination of a laterally expanded and somewhat dorsoventrally flattened carapace, anterior margin of the carapace excavate in dorsal view, uropod peduncles less than twice as long as pleonite 6, and subequal pleonites 4 and 5.